2019
DOI: 10.1038/s42003-019-0469-4
|View full text |Cite
|
Sign up to set email alerts
|

Ancient duplications and grass-specific transposition influenced the evolution of LEAFY transcription factor genes

Abstract: The LFY transcription factor gene family are important in the promotion of cell proliferation and floral development. Understanding their evolution offers an insight into floral development in plant evolution. Though a promiscuous transition intermediate and a gene duplication event within the LFY family had been identified previously, the early evolutionary path of this family remained elusive. Here, we reconstructed the LFY family phylogeny using maximum-likeliho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 75 publications
1
24
0
Order By: Relevance
“…AfLFY was also detected in roots, stems, leaves and young flower buds. This various expression pattern in the LFY homologs suggests the existence of a functional divergence and differentiated regulatory mechanisms associated with the flowers of different plants 33,65 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…AfLFY was also detected in roots, stems, leaves and young flower buds. This various expression pattern in the LFY homologs suggests the existence of a functional divergence and differentiated regulatory mechanisms associated with the flowers of different plants 33,65 .…”
Section: Discussionmentioning
confidence: 97%
“…The majority of seed-bearing plants examined to date contain one copy of LFY in their genomes 65 . However, multicopy genes have been found in some polyploids (e. g., eucalyptus, Monterey pine, and chrysanthemum) 30,36,63,66,67 , suggesting that LFY gene has experienced ancient transient duplications events, and that duplicated paralogues were promptly lost in most land plants thus maintaining LFY as a single copy 65 . In our study, two haplotypes were identified in six clones from A. frutescens; they shared more than 94% identity and were in the same clade, which indicated that gene flow might occur in A. frutescens.…”
Section: Discussionmentioning
confidence: 99%
“…Even in algae, mosses and ferns, LFY possesses a Sterile Alpha Motif domain, a highly conserved eukaryotic oligomerization domain [54]. The LFY family did not follow a classical expansion scheme and duplications were rarely retained except at the base of liverworts/moss and in gymnosperms, but the reasons for this remain elusive [55].…”
Section: Long Range Evolution Of Floral Tfsmentioning
confidence: 99%
“…The structure of this gene is relatively simple and well conserved in seed plants (Frohlich & Meyerowitz, 1997;Ma et al, 2016). Previous studies have shown that LFY exists as a single copy in most plants, even in the polyploid species (Riechmann & Ratcliffe, 2000;Shiu et al, 2005;Gao et al, 2019). LFY has been widely utilized to resolve relationships within angiosperm groups due to its low-copy and high nucleotide substitution rate (Dornelas & Rodriguez, 2006;Theissen & Melzer, 2007;Harris et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The LEAFY ( LFY ) gene was initially described in Antirrhinum majus and Arabidopsis thaliana (Coen et al, 1990; Schultz & Haughn, 1991) as a floral meristem identity gene that encodes a plant‐specific DNA‐binding transcription factor and plays a key role in regulating floral development (Moon et al, 2005; Gao et al, 2019; Hu et al, 2020). The structure of this gene is relatively simple and well conserved in seed plants (Frohlich & Meyerowitz, 1997; Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%